HOW DOES CONGESTION MATTER FOR JAKARTA’S CITIZENS? - Sonny Harry Budiutomo Harmadi (Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
Jakarta, as the biggest city in Indonesia, faces many problems, one of which is congestion, that produces a high cost economy. It is predicted that if the government does not take immediate action to solve this problem, there will be a potential loss of IDR65 trillion by 2020 (Bappenas, 2007). This consists of IDR28.1 trillion in operational costs and IDR36.9 trillion in opportunity costs from time lost. This study is aimed at estimating how much Jakarta citizens’ are willing to pay to overcome the congestion problem. By using the stated preference method, the estimation result shows that the annual cost of congestion in Jakarta is estimated at IDR50.2 trillion a year. Furthermore, this result can be used as a baseline for a cost-benefit analysis by the government to generate a better public transportation policy in Jakarta.Keywords: willingness to pay, congestion, stated preference method, conditional logit